Impact of a tilted coverslip on two-photon and STED microscopy - Le Bourdellès, Guillaume; Mercier, Luc; Roos, Johannes; Bancelin, Stéphane; Nägerl, U. Valentin (Biomedical optics express, 2024)
The advent of super-resolution microscopy has opened up new avenues to unveil brain structures with unprecedented spatial resolution in the living state. Yet, its application to live animals remains a genuine challenge. Getting optical access to the brain in vivo requires the use of a ‘cranial window’, whose mounting greatly influences image quality. Indeed, the coverslip used for the cranial window should lie as orthogonal as possible to the optical axis of the objective, or else significant optical aberrations occur. In this work, we assess the effect of the tilt angle of the coverslip on STED and two-photon microscopy, in particular, image brightness and spatial resolution. We then propose an approach to measure and reduce the tilt using a simple device added to the microscope, which can ensure orthogonality with a precision of 0.07°.